Explaining Support for Russian Narratives about the Events in Ukraine among Japanese Scholars and Intellectuals in 2014–19 - Hosaka, Sanshiro (Communist and post-communist studies, 2025)
Drawing on the concept of strategic narrative, this article explores how Russia’s issue narratives on the Ukraine events were reproduced by local narrative agents. I conducted content analysis of texts published in Japan from 2014 through 2019, and regression analysis to examine whether authors’ reproduction of Russia’s narratives is correlated to their affiliation with area studies branches (Russian studies, studies of other post-communist countries) and disciplines; epistemic linkage with the Kremlin-sponsored Valdai Discussion Club; and publication political stance (communist, progressive, conservative, neo-right) and types (peer-reviewed journals, think-tank reports, popular magazines). To investigate how issue narratives about the Ukraine events are associated with overarching system and identity narratives and Japanese local narratives, I generated boxplots and examined the distribution of the total scores of issue narratives for each narrative. The findings suggest that the affiliation with Russian studies is not an indicator of the reproduction of Russian narratives, whereas the active Valdai membership better explains the phenomenon. Alignment with specific views of the international system (system narratives such as “biased mainstream media”), Russia’s understanding of national identity (identity narratives such as “Russia-defensive” and “one people”), and aspirations for improved relations with Russia play a pivotal role in shaping one’s perceptions of the events in Ukraine.